Pelatihan Mesin Pirolisis untuk Pembuatan Liquid Smoke dalam Upaya Kemandirian Ekonomi di Desa Cilentung, Pandeglang - Junaedi, Yusup; Jaya Sutista, Ade; Mukhoyyaroh, Qiswatun; Nugraha; Maharani Particia, Vinda; Fajar Alamsyah, Indra (LOSARI: Jurnal Pengabdian Kepada Masyarakat, 2024)
This service is motivated by the abundance of natural resources owned by Cilentung Village, Pandeglang Regency. One of the main commodities is coconut where Cilentung Village is the top 10 supplier of coconuts in Pandeglang Regency. However, the utilization of coconuts has not been fully optimized by the local community because they only sell young coconuts to the city and the waste in the form of coconut fiber and shells is brought back to the village. So if left alone it will pollute the surrounding environment. The method of this service is a demonstration of the use of a pyrolysis machine to produce liquid smoke which has many benefits and high selling value. The results of the service stated that there was an increase in the skills of farmer groups by 84% and an increase in production by 85% because farmer groups can use pyrolysis machines to process coconut waste into derivative products in the form of liquid smoke.